The inner filter effects and their correction in fluorescence spectra of salt marsh humic matter - Mendonça, Ana (2018)
The inner filter effects in synchronous fluorescence spectra (δλ=60nm) of sedimentary humic substances from a salt marsh were studied. Accordingly to their type and the influence of plant colonization, these humic substances have different spectral features and the inner filter effects act in a different manner. The fluorescence spectra of the humic substances from sediments with colonizing plants have a protein like band (λexc=280nm) which is strongly affected by primary and secondary inner filter effects. These effects were also observed for the bands situated at longer wavelengths, i.e., at λexc=350nm and λex=454nm for the fulvic acids (FA) and humic acids (HA), respectively. However, they are more important for the band at 280nm, causing spectral distortions which can be clearly seen when the spectra of solutions 40mgL-1of different samples (Dissolved Organic Carbon - DOC~20mgL-1) are compared with and without correction of the inner filter effects. The importance of the spectral distortions caused by inner filter effects has been demonstrated in solutions containing a mixture of model compounds which represent the fluorophores detected in the spectra of sedimentary humic samples. The effectiveness of the mathematical correction of the inner filter effects in the spectra of those solutions and of solutions of sedimentary humic substances was studied. It was observed that inner filter effects in the sedimentary humic substances spectra can be mathematically corrected, allowing to obtain a linear relationship between the fluorescence intensity and humic substances concentration and preventing distortions at concentrations as high as 50mgL-1which otherwise would obscure the protein like band.